Assessment of landslide susceptibility: A case study of Carabao Mountain in Baguio city - Paringit, Maria Cecilia R. (Animo Repository, 2020)
Baguio City is one of the most visited places in the Philippines especially during the summer season. Due to its topography, soil characteristics, land use classification, and exposure to different calamities immense rainfall, Baguio City is prone to landslide. Lack of information and warning system regarding rainfall puts a challenge to decrease casualties and losses. The Carabao Mountain located in the north-left portion of Baguio City is chosen as the case study area because it is the most populated area. The degree of saturation of the soil and the imposed loading due to land use are considered as the main external factors for assessing the stability of earth slopes. Mohr-Coulomb failure criteria parameters are used in the determination of the initial factor of safety. Using different scenarios, a general factor of safety is obtained and then used to develop a landslide susceptibility map. The loading imposed by land-use developments such as settlement and road networks induces a great impact on the weight carried by the underlying soil which results in a greater decrease of the factor of safety. The impact of the saturation as an added weight to the soil is lower as compared to the loading of structures. The general factor of safety indicates that as the degree of saturation of soil increases, the moderate susceptible area increases, and some are close to a high susceptible degree with a factor of safety close to a value of 1, which is located at residential zone. Copyright © 2020, Int. J. of GEOMATE. All rights reserved.